Revisiting Theories of Humidity Transduction: A Focus on Electrophysiological Data - Tichy, Harald; Hellwig, Maria; Kallina, Wolfgang (Frontiers in Physiology, 2017)
Understanding the mechanism of humidity transduction calls for experimental data as well as a theory to interpret the data and to design new experiments. A comprehensive theory of humidity transduction must start with agreement on what humidity parameters are measured by hygroreceptors and processed by the brain. Hygroreceptors have been found in cuticular sensilla of a broad range of insect species. Their structural features are far from uniform. Nevertheless, these sensilla always contain an antagonistic pair of a moist cell and a dry cell combined with a thermoreceptive cold cell. The strategy behind this arrangement remains unclear. Three main models of humidity transduction have been proposed. Hygroreceptors could operate as mechanical hygrometers, psychrometers or evaporation detectors. Each mode of action measures a different humidity parameter. Mechanical hygrometers measure the relative humidity, psychrometers indicate the wet-bulb temperature, and evaporimeters refer to the saturation deficit of the air. Here we assess the validity of the different functions by testing specific predictions drawn from each of the models. The effect of air temperature on the responses to humidity stimulation rules out the mechanical hygrometer function, but it supports the psychrometer function and highlights the action as evaporation rate detector. We suggest testing the effect of the flow rate of the air stream used for humidity stimulation. As the wind speed strongly affects the power of evaporation, experiments with changing saturation deficit at different flow rates would improve our knowledge on humidity transduction.